Granuloma annulare and SARS-CoV-2 pandemic. - Mazzotta, F.; Troccoli, T.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
Granuloma annulare is a disease with well-defined and constant clinical characteristics, although it can be caused by multiple factors. Among the latter the most frequent are viral agents. Based on the history, some of its clinical oddities in time of COVID-19 and some pathogenetic and histological similarities with vasculitis induced by SARS-CoV-2 the Authors believe that granuloma annulare at the time of COVID-19 in some cases may be due to SARS-CoV-2.